2000
DOI: 10.1152/ajpendo.2000.279.1.e124
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss in postmenopausal obesity: no adverse alterations in body composition and protein metabolism

Abstract: We sought to determine if decrements in the mass of fat-free body mass (FFM) and other lean tissue compartments, and related changes in protein metabolism, are appropriate for weight loss in obese older women. Subjects were 14 healthy weight-stable obese (BMI > or =30 kg/m(2)) postmenopausal women >55 yr who participated in a 16-wk, 1, 200 kcal/day nutritionally complete diet. Measures at baseline and 16 wk included FFM and appendicular lean soft tissue (LST) by dual-energy X-ray absorptiometry; body cell mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
1
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 33 publications
(42 reference statements)
3
50
1
2
Order By: Relevance
“…Therefore, the more BCM that is preserved, the greater the likelihood of weight loss and maintaining the weight lost. Gallagher et al (2000) also reported a significant weight loss with a concomitant maintenance of FFM following a 16-week 1200 kcal/day hypoenergetic diet in postmenopausal obese. Gallagher et al (2000) stated, 'Weight loss was accompanied by body composition and protein kinetic changes that appear appropriate for the magnitude of body mass change, thus failing to support the concern that dietinduced weight loss in obese postmenopausal women produces disproportionate LST (lean soft tissue) losses'.…”
Section: Anthropometric and Body Composition Changesmentioning
confidence: 87%
See 1 more Smart Citation
“…Therefore, the more BCM that is preserved, the greater the likelihood of weight loss and maintaining the weight lost. Gallagher et al (2000) also reported a significant weight loss with a concomitant maintenance of FFM following a 16-week 1200 kcal/day hypoenergetic diet in postmenopausal obese. Gallagher et al (2000) stated, 'Weight loss was accompanied by body composition and protein kinetic changes that appear appropriate for the magnitude of body mass change, thus failing to support the concern that dietinduced weight loss in obese postmenopausal women produces disproportionate LST (lean soft tissue) losses'.…”
Section: Anthropometric and Body Composition Changesmentioning
confidence: 87%
“…Gallagher et al (2000) also reported a significant weight loss with a concomitant maintenance of FFM following a 16-week 1200 kcal/day hypoenergetic diet in postmenopausal obese. Gallagher et al (2000) stated, 'Weight loss was accompanied by body composition and protein kinetic changes that appear appropriate for the magnitude of body mass change, thus failing to support the concern that dietinduced weight loss in obese postmenopausal women produces disproportionate LST (lean soft tissue) losses'. Our findings suggest that a small and appropriate fraction of weight loss consists of FFM that we can attribute to water loss; however, BCM was maintained, and the majority of weight loss was due to loss of FM.…”
Section: Anthropometric and Body Composition Changesmentioning
confidence: 87%
“…The protocol involved the acquisition of approximately 40 axial images, 10 mm thickness, and at 40 mm intervals across the whole body. 24,25 Images were analyzed using VECT image analysis software (Martel, Montreal, Canada) on a Sun Workstation (Silicon Graphics, Mountain View, CA, USA). Abdominal adipose tissue was calculated using seven slices, of which four were above and two below the L4 -5 level.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…26 The technical errors for repeated measurements of the same scan by the same observer of MRI-derived TAT and VAT volumes in our laboratory are 1.1 AE 1.2% and 1.1 AE 1.5%, respectively. 25 …”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…But in moderate and extreme obesity, percent body fat increases greatly, resulting in a relatively smaller TBW compartment. Following conventional weight loss in the obese, large decreases in FM and relative shifts in body water compartments are observed (Gallagher et al, 2000), and similar changes have been reported following massive weight loss in the morbidly obese undergoing gastric bypass surgery (Das et al, 2003). The use of stable isotopes has greatly facilitated the accurate measurement of such changes with weight loss and in understanding these physiological states.…”
Section: Body Compositionmentioning
confidence: 67%